Effectiveness of an Organic Mask of Moringa Leaves (Moringa oleifera) and Turmeric (Curcuma longa) for Facial Care - Agusriani, Agusriani; Hamilatussa'diyah, Hamilatussa'diyah; Azizah, Lailan; Fitrianingsih, Fitrianingsih (Jurnal Kefarmasian Indonesia, 2024)
Facial masks are cosmetic products for topical use on facial skin. Using organic components from nature can prevent irritation and skin pigment damage due to the side effects of harmful chemicals in cosmetic products in the global market. This study aims to develop a combination organic mask formulation from Moringa leaves and turmeric and test its effectiveness. This experimental study, which had a one-shot case study design, was conducted at the Pharmaceutical Technology Laboratory and Phytochemical Laboratory, Pharmacy Department, Health Polytechnic, Ministry of Health, Jambi. The formulation consisted of Moringa leaf powder and turmeric with formulas F1 (40%, 30%), F2 (50%, 25%) and F3 (60%, 20%). Further data analysis used the paired t-test. The evaluation consists of phytochemical screening, characteristic tests of the organic mask (organoleptic, pH, drying time, and homogeneity), stability tests (organoleptic, fungal growth), effectiveness tests of mask preparations (skin moisture), and antioxidant activity tests. Based on the results, formula 3 showed the best results as an organic mask preparation with moisture test results of 58.87 ± 6.24 (mean ± SD), p <0.001. The antioxidant activity results showed IC50 values of each formula were F1 (73.43 µg/ml), F2 (56.33 µg/ml), and F3 (182.11 µg/ml). This study recommends that Moringa leaves and turmeric have potential and effectiveness as antioxidant compounds that can be developed as organic mask preparations.